Tyrosine kinases as essential cellular cofactors and potential therapeutic targets for human immunodeficiency virus infection - Bertoletti, F.; Crespan, E.; Maga, G. (Cellular and Molecular Biology, 2012)
The Human Immunodeficiency Virus (HIV) is the cause of the AIDS disease. To date, more than 30 million people worldwide are infected with HIV-1, which causes two millions deaths each year. The pandemic is still ongoing, with three million new infections every year. Even though the current arsenal of anti-HIV drugs is composed of more than twenty different molecules, it became clear that the chemotherapeutic approach will not be able to cure AIDS, at least in its current form. It is essential, in order to develop more effective ways of treating this disease, to better understand the interplay of HIV with its cellular host, in fact HIV-1 is an obligatory intracellular parasite that takes advantage of the host cell metabolism for its own replication. HIV-1 takes control of virtually every aspect of cell metabolism by changing the functional properties of key signaling cellular proteins, thus triggering virus-specific signal transduction pathways. In this review, we will summarize the current knowledge about the role(s) of cellular tyrosine kinases in HIV infection and their potential therapeutic exploitation.